2015
DOI: 10.1111/ele.12448
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity mediates top–down control in eelgrass ecosystems: a global comparative‐experimental approach

Abstract: Nutrient pollution and reduced grazing each can stimulate algal blooms as shown by numerous experiments. But because experiments rarely incorporate natural variation in environmental factors and biodiversity, conditions determining the relative strength of bottom-up and top-down forcing remain unresolved. We factorially added nutrients and reduced grazing at 15 sites across the range of the marine foundation species eelgrass (Zostera marina) to quantify how top-down and bottom-up control interact with natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
212
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(218 citation statements)
references
References 51 publications
4
212
2
Order By: Relevance
“…By fitting multiple models to a series of response variables, SEMs have the capacity to rigorously estimate indirect effects and causal links within complex networks (Grace 2006;Duffy et al 2015). Piecewise SEMs incorporate several linear models into a single causal pathway analysis using directional separation (d-separation) tests (series of independence claims that statistically identify causal relationships and missing links (i.e.…”
Section: Fit Of Data To a Theoretical Trophic Cascadementioning
confidence: 99%
“…By fitting multiple models to a series of response variables, SEMs have the capacity to rigorously estimate indirect effects and causal links within complex networks (Grace 2006;Duffy et al 2015). Piecewise SEMs incorporate several linear models into a single causal pathway analysis using directional separation (d-separation) tests (series of independence claims that statistically identify causal relationships and missing links (i.e.…”
Section: Fit Of Data To a Theoretical Trophic Cascadementioning
confidence: 99%
“…One widespread species, Zostera marina, or eelgrass, in particular, provides a habitat for ecologically diverse and economically important ecosystems along coasts throughout much of the Northern Hemisphere (16,17). The return of terrestrial seagrass ancestors to oceans is among the most severe habitat shifts accomplished by vascular plants (18) and has prompted detailed study of the physiological adaptations associated with this shift (19,20), including the tolerance of salinity and anoxic sediment conditions.…”
mentioning
confidence: 99%
“…The presence and diversity of a mesograzer community are important for controlling epiphytic algae (Duffy, 2002). Global experimental studies on Z. marina have demonstrated that diversity of the invertebrate mesograzer community is comparably important to global change stressors in the top-down control of seagrass ecosystems (Duffy et al, 2015).…”
Section: Trophic Interactionsmentioning
confidence: 99%